2019
DOI: 10.3390/su11236589
|View full text |Cite
|
Sign up to set email alerts
|

From Students’ Personal and Social Responsibility to Autonomy in Physical Education Classes

Abstract: The objective of this study was to analyze the effect that the application of the personal and social responsibility model has on students’ perception of a teacher’s interpersonal style and on the perception of autonomy. A quasi-experimental design was used with a control group (n = 60) and an experimental group (n = 60) to which the intervention was applied. Participants were aged between 10 and 13 years. As the main results, the experimental group saw improvements in support for the autonomous interpersonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
2
13
0
1
Order By: Relevance
“…As expected in the initial hypothesis, the athletes who participated in the experimental group obtained significant improvements in social responsibility over those in the control group after participating in the program. These results coincide with other investigations that have found an improvement in responsibility behaviors after an intervention program based on Hellison's responsibility model (Hellison and Walsh, 2002;Gordon, 2007, unpublished;Wright and Burton, 2008;Lee and Martinek, 2009;Hayden, 2010;Caballero Blanco, 2012;Escartí et al, 2012;Bean and Forneris, 2015;Valero-Valenzuela et al, 2019). The situations in which adolescents present higher indices of responsibility are those related to the ability to show respect for others, help others, be kind to others, control impulses, and collaborate with others.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected in the initial hypothesis, the athletes who participated in the experimental group obtained significant improvements in social responsibility over those in the control group after participating in the program. These results coincide with other investigations that have found an improvement in responsibility behaviors after an intervention program based on Hellison's responsibility model (Hellison and Walsh, 2002;Gordon, 2007, unpublished;Wright and Burton, 2008;Lee and Martinek, 2009;Hayden, 2010;Caballero Blanco, 2012;Escartí et al, 2012;Bean and Forneris, 2015;Valero-Valenzuela et al, 2019). The situations in which adolescents present higher indices of responsibility are those related to the ability to show respect for others, help others, be kind to others, control impulses, and collaborate with others.…”
Section: Discussionsupporting
confidence: 90%
“…Teaching personal and social responsibility interventions have shown a positive improvement in self-efficacy, prosocial behaviors, and personal and social responsibility ( Escartí et al, 2005 , 2010 , 2012 , 2013 ; Alcalá et al, 2019 ; Valero-Valenzuela et al, 2019 ). Self-efficacy refers to “belief in one’s capabilities to organize and execute the courses of action required to produce given attainments” ( Bandura, 1997 , p. 3).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it is observed how both variables positively and significantly predicted students’ prosocial behavior. Valero-Valenzuela et al [ 72 ] conclude that the use of teaching models that promote the support of autonomy through the assignment of responsibilities produce multiple benefits, among which the satisfaction of students’ BPN, primarily that of autonomy, stands out. This need shows a negative correlation with variables to be eradicated in the educational context, such as violent or disruptive behavior [ 7 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In short, it seems that social responsibility and the progressive development of moral autonomy are linked (Osler and Starkey, 2005), and research with adolescents has found positive and predictive relationships between them Gutiérrez et al, 2011). Responsibility programs play a fundamental role in the development of autonomy (Ellison et al, 2019;Valero-Valenzuela et al, 2019); contributing to the improvement of cognitive skills (Jukes et al, 2018); the perception of competence and intrinsic motivation (Manzano-Sánchez and Valero-Valenzuela, 2019); fun, satisfaction with life, empathy, and prosocial behavior (Cecchini et al, 2003;Gutiérrez et al, 2011); and education in values in general (Sánchez-Alcaraz et al, 2016). When the community is involved, these programs also help to minimize aggressive behavior (Lorenzo-Seva et al, 2010) and improve contexts other than the context in which the program was implemented (Caballero et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Responsibility is considered as the ability to respond to one's actions appropriately and effectively in accordance with the social norms (Keller, 2012). The teaching of this value should occur mainly in the educational and family spheres (Geboers et al, 2012), as it has a direct effect on academic performance and commitment (Carbonero et al, 2015) and on personal autonomy (Valero-Valenzuela et al, 2019). However, it should be implemented in everyday situations (Shiller, 2013), which should go beyond the private realm (Caba-Collado et al, 2016).…”
Section: Introductionmentioning
confidence: 99%